Enhanced CO2 Capture Potential of Chitosan-Based Composite Beads by Adding Activated Carbon from Coffee Grounds and Crosslinking with Epichlorohydrin - Vorrada Loryuenyong; Worranuch Nakhlo; Praifha Srikaenkaew; Panpassa Yaidee; Achanai Buasri; Apiluck Eiad-Ua (My University, 2024)
Carbon dioxide (CO2) capture has been identified as a potential technology for reducing the anthropic emissions of greenhouse gases, particularly in post-combustion processes. The development of adsorbents for carbon capture and storage is expanding at a rapid rate. This article presents a novel sustainable synthesis method for the production of chitosan/activated carbon CO2 adsorbents. Chitosan is a biopolymer that is naturally abundant and contains amino groups (–NH2), which are required for the selective adsorption of CO2. Spent coffee grounds have been considered as a potential feedstock for the synthesis of activated coffee grounds through carbonization and chemical activation. The chitosan/activated coffee ground composite microspheres were created using the emulsion cross-linking method with epichlorohydrin. The effects of the amount of chitosan (15, 20, and 25 g), activated coffee ground (10, 20, 30, and 40%w/w), and epichlorohydrin (2, 3, 4, 5, 6, 7 and 8 g) were examined. The CO2 capture potential of the composite beads is superior to that of the neat biopolymer beads. The CO2 adsorbed of synthesized materials at a standard temperature and pressure is improved by increasing the quantity of activated coffee ground and epichlorohydrin. These findings suggest that the novel composite bead has the potential to be applied in CO2 separation applications.
Keywords: Epichlorohydrin; Biopolymer; Carbon Dioxide Capture Technologies